Health Perceptions and Mental Well-Being: A LASI-Based Study of Depression in Indian Older Adults - Paul, Shanku; Das, Jayashree; Das, Dipankaj; Paul, Ujjal (National Journal of Community Medicine, 2025)
Background: Depression among older adults is an emerging public health challenge in India, often influenced by complex interactions between physical health and socio-demographic factors. While self-rated health is a widely recognized determinant of overall well-being, its association with depression in the Indian older adults remains underexamined. The objective was to assess the relationship between self-rated health and depression among older Indian adults, while adjusting for demographic, socioeconomic, and health-related variables. Methods: Data were drawn from the Longitudinal Ageing Study in India (LASI, Wave 1), including 64,695 individuals aged 45 and above. Depression was measured using the CES-D 10-item scale, with scores 4 or above indicating likely depression. Self-rated health was categorized as good, average, or poor. A multivariable binary logistic regression model was used to estimate adjusted odds ratios (AOR) with 95% confidence intervals (CI), accounting for complex survey design. Results: Older adults reporting poor self-rated health had significantly higher odds of depression (AOR = 2.47, 95% CI: 2.36–2.59), and those with average health also showed increased odds (AOR = 1.46, 95% CI: 1.42–1.50), compared to those reporting good health. Other significant predictors included lower education (e.g., up to secondary: AOR = 0.56, 95% CI: 0.50–0.64), female (AOR = 1.07, 95% CI: 1.01–1.13), single marital status (AOR = 1.46, 95% CI: 1.32–1.61), functional limitations (AOR = 1.39, 95% CI: 1.31–1.47), and multimorbidity (AOR = 1.77, 95% CI: 1.54–2.03). Dissatisfaction with living arrangements was also strongly associated with depression (AOR = 2.83, 95% CI: 2.42–3.31). Conclusion: Self-rated health is a robust predictor of depression among older adults in India. These findings highlight the urgent need for integrated health and social care strategies that consider both physical health and social determinants to reduce the mental health burden in aging populations.